(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The star at the middle of the solar system is the Sun. It consists of hot plasma interwoven with magnetic fields and is almost perfectly spherical. The sun is a star of the G2V main sequence and thus produces its energy by the nuclear fusion of nuclei of hydrogen into helium. At its heart, 620 million metric tonnes of hydrogen is fused into the sun every second. The radioactive zone and the convective zone surround the nucleus. There are three layers of the solar atmosphere the photosphere, the chromospheres and the corona. Above the convective zone is the photosphere and most of the sunlight is produced from this area. The temperature of the photosphere is between around 5800 K and 6050 K. Bright, bubbling granules of plasma and darker, cooler sunspots mark the photosphere. The inner dark cool region is called the umbra and the penumbra is known as the outer relatively light sunspot region. Above the photosphere lie the chromospheres and corona. The sun’s gentle X-ray pictures display coronal loops and light points. Where the magnetic field is open and from which the solar wind streams outward, coronal holes are seen. Due to magnetic reconnection, solar flares and coronal mass ejections are thought to occur. This CME produces massive interplanetary magnetic field (IMF) disturbances that are responsible for generating cosmic ray Geomagnetic Storms (GSs) and for bush Decrease (FDs).